Police story and emotions - DADCI, Mohamed Salah (Journal of Human Sciences, 2022)
With regard to the theory of story-telling, specialists are commonly familiar, on the one hand, with the Thematic Narratology (Propp, Greimas, Larivaille…), which focuses on the content of the story and on the different adventures that make it; and, on the other hand , with the Discursive Naratology (Gérard Genette), which analyses types of narrative discourse. In addition to this Traditional Narratology, a Post- traditional Narratology has been developed with a view of studying the thymic functions of a narrative; in other words, how setting the plot creates a narrative tension, which, itself, creates emotions in the reader of the work. In this perspective, the research works of Raphaël Baroni are pertinent examples of Post- traditional Narratology. We have used Raphaël Baroni’s woks, in this article, to analyse ‘suspense’, ‘curiosity’, and ‘surprise’ in the immersive story. To better demonstrate and back our analysis with evidence, we have relied on two detective stories of Pierre Lemaître, Alex and Robe de marié